PENGEMBANGAN MEDIA PEMBELAJARAN BONEKA JARI TEMA INDAHNYA KERAGAMAN DI NEGERIKU UNTUK MENINGKATKAN NILAI KARAKTER KELAS IV DI SDN BLURU KIDUL 2 - indriana (PRODI PGSD UNIVERSITAS PGRI DELTA, 2020)
Learning media is part of the achievement of learning objectives. Learning media can help overcome the difficulties of students in understanding the material being taught by the teacher. The purpose of this development research is to develop finger puppet media learning media used in thematic learning on the theme of the Beauty of Diversity in My Country for grade IV SD, to determine whether student activity is active or not when using finger puppet learning media, and with the hope that learning media can be used effectively. The method used in this research is the development of Borg and Gall modified by Sugiyono. The steps taken in this research and development are: 1) potentials and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product testing, 7) product revision. The subjects of this research trial were students of grade IV SD, with two stages, namely: the pre-test and post-test subjects totaling 8 people due to the limitations of researchers in conducting research in the era of the COVID-19 pandemic. Data collection techniques used questionnaires, tests, and observations. The data analysis technique used is data analysis from qualitative to quantitative data. The results of the research on the development of finger puppet media have received very appropriate information according to the validation of material experts and media experts after carrying out 2 stages of validation with each obtaining 91% and 85% and the pretest and posttest results of 68% and 95%. The results of the observations that were assessed by the teacher when the researcher were doing teaching activities obtained a percentage of 91.3% with very decent information